(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The medical professionals who operate in hospital emergency departments (EDs) face a wide range of organizational and operational stresses due to the nature of their job. Examine the mental and emotional conditions in which emergency department nurses, paramedics, and doctors work at one particular hospital. Specifically, look at 1) job duties 2) regulating scales 4) the staff’s anticipated adjustments, and 3) the individual’s psycho-physical health. The study included seventy-four emergency department workers (nurses, paramedics, and doctors) from a Saudi Arabian university clinical hospital. The Psychosocial Working Conditions Questionnaire (PWCQ), a standardized tool, was used. The average ratings on the following scales were as follows: demands (94.99), control (59.26), social support (48.94), and desired changes (75.32). The longer someone has been with the company, the less help they get on the job (r=-0.308, p=0.01). At the same time, those living in towns and villages with less than 100,000 inhabitants saw a greater need for workplace improvements (p=0.007). A substantial correlation (p<0.05) was found between the respondents’ material status and the responses obtained from each subscale of the PWCQ questionnaire. Compared to nurses (44.39±10.26), paramedics (51.11±8.48) and physicians (52.95±13.66) reported considerably greater levels of workplace support (p=0.005). The psychosocial working conditions and plenty of stresses in the emergency department necessitate that companies take action to improve them.